A laparoscopic procedure for the treatment of uterine prolapse during pregnancy: A case series. (November 2019) - Yildiz, M. Serhat; Ekmekci, Emre
Abstract: Objective: To demonstrate the outcomes of pregnancies with uterine prolapse who have undergone laparoscopic suspension via a new approach during the first and second trimesters. Design: Retrospective case series study. Patients: Three patients who had undergone surgical procedures for uterine prolapse during pregnancy. Interventions: Laparoscopic treatment of uterine prolapse involves a procedure called 'vaginal assisted laparoscopic sacrocervicopexy'. The complications and difficulties of each case are described. Results: The patients underwent surgical procedures at 12, 14 and 16 weeks of pregnancy. All cases were delivered at term. As the gestational age increased, the operation became more difficult and the operation time was prolonged. The patient who delivered vaginally was complicated with shoulder dystocia. Conclusion: Three successful cases of uterine prolapse surgery during pregnancy are reported. Surgery can be performed during pregnancy if absolutely necessary, and does not need to be delayed until the postpartum period.